3D-printed bioactive scaffolds from nanosilicates and PEOT/PBT for bone tissue engineering. Issue 1 (15th December 2018) - Carrow, James K; Di Luca, Andrea; Dolatshahi-Pirouz, Alireza; Moroni, Lorenzo; Gaharwar, Akhilesh K
Abstract: Additive manufacturing (AM) has shown promise in designing 3D scaffold for regenerative medicine. However, many synthetic biomaterials used for AM are bioinert. Here, we report synthesis of bioactive nanocomposites from a poly(ethylene oxide terephthalate) (PEOT)/poly(butylene terephthalate) (PBT) (PEOT/PBT) copolymer and 2D nanosilicates for fabricating 3D scaffolds for bone tissue engineering. PEOT/PBT have been shown to support calcification and bone bonding ability in vivo, while 2D nanosilicates induce osteogenic differentiation of human mesenchymal stem cells (hMSCs) in absence of osteoinductive agents. The effect of nanosilicates addition to PEOT/PBT on structural, mechanical and biological properties is investigated. Specifically, the addition of nanosilicate to PEOT/PBT improves the stability of nanocomposites in physiological conditions, as nanosilicate suppressed the degradation rate of copolymer. However, no significant increase in the mechanical stiffness of scaffold due to the addition of nanosilicates is observed. The addition of nanosilicates to PEOT/PBT improves the bioactive properties of AM nanocomposites as demonstrated in vitro. hMSCs readily proliferated on the scaffolds containing nanosilicates and resulted in significant upregulation of osteo-related proteins and production of mineralized matrix. The synergistic ability of nanosilicates and PEOT/PBT can be utilized for designing bioactive scaffolds for bone tissue engineering.